Disordered eating in sexual and gender minority adults: the roles of gender variance, appearance anxiety, and internalized ideals - Micu, Ana-Sofia; Godeanu, Alin-Sebastian; Constantin, Vasile (Frontiers in Psychology, 2025)
IntroductionSexual and gender minority (SGM) individuals face elevated risks for disordered eating and body image disturbances, shaped by minority stress, internalized beauty norms, and gendered societal expectations. This study examined (1) whether SGM individuals in Romania report higher levels of disordered eating than cisgender heterosexuals, and (2) whether appearance-related anxiety and internalized beauty ideals mediate the relationship between gender identity/expression and disordered eating within the SGM group.MethodsA total of 270 Romanian adults (aged 18+), including 225 identifying as SGM, completed self-report measures of disordered eating, gender variance, femininity, appearance-related social anxiety, and thin-ideal internalization. Statistical analyses included Mann–Whitney U tests, bivariate correlations, and percentile bootstrap mediation models.ResultsSexual and gender minority participants reported significantly higher disordered eating symptoms than cisgender heterosexuals. In the SGM group, social appearance anxiety partially mediated the relationship between gender variance and disordered eating (β = 0.1036, p = 0.008), while gender variance showed a significant negative direct effect (β = −0.1465, p = 0.009). The indirect effect of femininity through thin-ideal internalization was marginal (β = 0.0852, p = 0.051). Both appearance-related anxiety (β = 0.5715, p < 0.001) and thin-ideal internalization (β = 0.6549, p < 0.001) were robust predictors of disordered eating.DiscussionFindings underscore the heightened vulnerability of Romanian SGM individuals to disordered eating and illuminate the dual role of gender expression as both a stressor and a potential protective factor. Appearance-related anxiety and internalized ideals emerged as key mechanisms, though with nuanced and partly inconsistent effects. By situating these processes within an under-researched Eastern European context, the study contributes culturally specific insights to the global literature on SGM health disparities. Future research should employ intersectional designs and incorporate broader constructs such as muscularity-oriented dissatisfaction and compensatory behaviors.